ЎЗБЕКИСТОНДА МИЛЛАТЛАРАРО ТОТУВЛИКНИ ТАЪМИНЛАШНИНГ ҲУҚУҚИЙ АСОСЛАРИ ВА УСТУВОР ЙЎНАЛИШЛАРИ - Қутлымуратов, Ф.Қ.; Хабибуллаева, Д.К. (SCIENCE and SOCIETY, 2020)
The article describes legal bases and priority directions of ensuring interethnic harmony in Uzbekistan.
Keywords: strategy of actions; assembly of nations; nation; constitution; freedom of conscience; religious tolerance